Peran Guru Madrasah Ibtidaiyah dalam Membentuk Karakter Islami pada Peserta Didik - Destia Muliana; Syamzaimar Syamzaimar (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
This study aims to examine the role of Madrasah Ibtidaiyah teachers in shaping students’ Islamic character through a character education approach. The research employs a qualitative method with a library research design by reviewing various literature sources, including books, journal articles, and relevant previous studies. The findings indicate that Madrasah Ibtidaiyah teachers play a strategic role as educators, mentors, role models, facilitators, and guides in instilling Islamic character values in students from an early age. These values include honesty, discipline, responsibility, patience, empathy, humility, gratitude, mutual respect, cooperation, and obedience to Islamic teachings. The formation of Islamic character is carried out through classroom learning activities, daily habituation, exemplary behavior demonstrated by teachers, and various religious programs integrated into school life, such as congregational prayers, Qur’an recitation, and Islamic celebrations. In addition, teachers collaborate with parents and the school environment to create a consistent and supportive atmosphere for character development. The study concludes that the success of Islamic character education at the Madrasah Ibtidaiyah level is strongly influenced by the consistency, commitment, and quality of teachers’ roles in carrying out their educational responsibilities and serving as positive examples for students in everyday life.